Предмет: Алгебра,
автор: lizabk02
решите уравнение (х-3)+6х=2(2х-1)-3(4-х)
Ответы
Автор ответа:
0
x-3+6x=4x-2-12+3x
x-3+6x-4x+2+12-3x=0
-x+11=0
x-11=0
= 0
= 11
x-3+6x-4x+2+12-3x=0
-x+11=0
x-11=0
= 0
= 11
Автор ответа:
0
а почему -х,если х+6х-4х-3х равно 0?
Автор ответа:
0
(х-3)+6х=2(2х-1)-3(4-х)
х-3+6х=4х-2-12+3х
х+6х-4х-3х=-2-12+3
0х=-11
ответ 0
х-3+6х=4х-2-12+3х
х+6х-4х-3х=-2-12+3
0х=-11
ответ 0
Похожие вопросы
Предмет: Химия,
автор: VadimVoronin2005
Предмет: Математика,
автор: dianadeg0707
Предмет: История,
автор: 2008alinka200885
Предмет: Химия,
автор: Аноним
Предмет: Математика,
автор: elenagoncharen